2010
DOI: 10.1038/ismej.2010.36
|View full text |Cite|
|
Sign up to set email alerts
|

Significant CO2 fixation by small prymnesiophytes in the subtropical and tropical northeast Atlantic Ocean

Abstract: Global estimates indicate the oceans are responsible for approximately half of the carbon dioxide fixed on Earth. Organisms p5 lm in size dominate open ocean phytoplankton communities in terms of abundance and CO 2 fixation, with the cyanobacterial genera Prochlorococcus and Synechococcus numerically the most abundant and more extensively studied compared with small eukaryotes. However, the contribution of specific taxonomic groups to marine CO 2 fixation is still poorly known. In this study, we show that amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
278
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 270 publications
(317 citation statements)
references
References 66 publications
29
278
1
1
Order By: Relevance
“…The high Prymnesiophyceae signal detected across all ocean basins (Supplementary Table 3) supports the observation that 19 0 -hexanoyloxyfucoxanthin, a prymnesiophyte-specific pigment (though also present in a few other Heterokont algae, see Andersen, 2004), often dominates oceanic pigment analyses Liu et al, 2009). Recent fluorescent in situ hybridisation studies confirm the high abundance of these pico-prymnesiophytes in the Atlantic Ocean (Jardillier et al, 2010;Grob et al, 2011;Kirkham et al, 2011b), Indian Ocean and in open ocean regions of the Arctic Ocean . However, Prymnesiophyceae have been consistently underestimated in previous amplificationbased studies using primers targeting the nuclear 18S rRNA gene, potentially a result of PCR bias (Liu et al, 2009).…”
Section: Ppe B-diversitysupporting
confidence: 63%
See 3 more Smart Citations
“…The high Prymnesiophyceae signal detected across all ocean basins (Supplementary Table 3) supports the observation that 19 0 -hexanoyloxyfucoxanthin, a prymnesiophyte-specific pigment (though also present in a few other Heterokont algae, see Andersen, 2004), often dominates oceanic pigment analyses Liu et al, 2009). Recent fluorescent in situ hybridisation studies confirm the high abundance of these pico-prymnesiophytes in the Atlantic Ocean (Jardillier et al, 2010;Grob et al, 2011;Kirkham et al, 2011b), Indian Ocean and in open ocean regions of the Arctic Ocean . However, Prymnesiophyceae have been consistently underestimated in previous amplificationbased studies using primers targeting the nuclear 18S rRNA gene, potentially a result of PCR bias (Liu et al, 2009).…”
Section: Ppe B-diversitysupporting
confidence: 63%
“…Although there is a general trend in the PPE/total picophytoplankton (that is, PPEs þ picocyanobacteria) ratio increasing systematically with increasing latitude and decreasing temperature (Bouman et al, 2012), a considerable amount of variability is observed across the range of latitudes and temperatures. It is important to remember that even at very low cell abundances, PPEs are now known to contribute significantly to marine primary production because of a multifactorial effect of greater biovolume, higher growth rates and high grazing mortality rates (Li, 1994;Worden et al, 2004;Jardillier et al, 2010;Grob et al, 2011). Marine PPE community structure AR Kirkham et al PPE a-diversity Clone sequence data of the 16S rDNA from all the transects studied here (except the BEAGLE and Indian Ocean transects) representing 31 clone libraries allowed us to calculate species richness values (a-diversity) using the Margalef index (Dmg) ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microbial eukaryotes have key roles in marine ecosystems, particularly in primary production, nutrient cycling as well as for food-web dynamics (Sherr and Sherr, 2008;Jardillier et al, 2010;Caron et al, 2012). Among heterotrophic protists, small flagellates (1-5 mm) constitute a key link between bacteria and larger protists, transferring organic carbon to upper trophic levels (Jurgens and Massana, 2008;Massana, 2011).…”
Section: Introductionmentioning
confidence: 99%